Visualizing InfoVis Researchers with ContactTrees - Sallaberry, Arnaud; Ma, Kwan-Liu (Poster session of IEEE InfoVis'12, 2012)
This poster presents an application of ContactTree, a new ego-centered visualization design, to charactering the collaborative activities of selected InfoVis researchers in terms of their publications as listed in DBLP. The ContactTree visualization, based on a botanical tree metaphor, is designed for studying individuals and comparing their social behavior and relationships with others based on data with rich attributes. As shown, the resulting trees give each of the selected researchers a distinct look, and many interesting patterns reveal themselves. In social science research, the study of people's social contacts and activities is of high interest. ContactTree visualization well complements conventional network visualization, which is better for showing relations among people and activities in a global context.